The Aesthetics of Textural Ambiguity: Brahms and the Changing Piano - Augustus Arnone (Current Musicology, 2006)
In recent years, a number of performance practice scholars writing on Brahms’s piano music have commented on the prominence of low-lying melodic lines, thickly-written accompaniments, and often dense saturation of the lower register. For such writers these textural features constitute proof that Brahms could not have intended performance on the modern piano. Firms such as Steinway, Bechstein, and Chickering were manufacturing pianos by the early 1860s, roughly the midpoint of Brahms’s life, that already exhibited most of the important design innovations that distinguish modern pianos from earlier ones, and these firms enjoyed enormous success across Europe. Performance practice scholars have argued that the increased power and sustain of these pianos create irreparable problems of balance and clarity in much of Brahms’s music, implying that he was writing for the lighter and more transparent instruments that predate the modern piano, many of which were still manufactured up until the end of the century.